Pinctada Maxima Pearl Shells as a Promising Bone Graft Material in the World of Dentistry - Chandha, M. Hendra; Mappangara, Surijana; Achmad, Harun; Oktawati, Sri; Ramadhan, Sitti Raoda Juanita; Yudin, Muhammad; Asri, Gustivanny Dwipa (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Pinctada maxima pearl shell contains inorganic and organic materials that have a bone-like basic structure that facilitates bone remodeling. AIM: This study aimed to describe the effectiveness of Pinctada maxima pearl shells as bone graft material in the world of dentistry using an animal model. METHODS: Research uses Pinctada maxima pearl shell that was processed into hydroxyapatite Pinctada maxima (HPM) powder. Chemical and surface characteristics of HPM were performed with X-ray fluorescence (XRF), Fourier transform infra-red (FTIR), and X-ray diffraction (XRD), respectively. Thirty male guinea pigs were randomly assigned into three groups: Negative control (NC), positive control, and HPM. After 14–21 days of observation, guinea pigs were sacrificed. Bone formation was seen through immunohistochemical examination of osteoprotegerin (OPG) and bone morphogenetic protein (BMP2) expression. Data were analyzed through Shapiro wills and analysis of variance with a significance level of 5%. RESULTS: There was a high expression of OPG and BMP2 on days 14–21 in the HPM group when compared to the NC group with a significance level of 5%. CONCLUSION: HPM powder can be used as a promising bone graft material in the world of dentistry.